Benefit finding in cancer: The argument of being positive - Kassianos, Angelos P. (My University, 2013)
For years, cancer-research has been focused on negative outcomes on patients' lives and well-being. The diagnosis itself can be extremely stressful and have severe consequences for patients, like depression, anxiety, and distress. Consequently it can worsen their Quality of Life (QoL). What makes cancer diagnosis stressful while triggering change is the uncontrollable, sudden and unexpected nature of diagnosis, which produces ongoing, and in many cases lifelong effects and stressors (Andrykowski et al., 1998). However, colorectal cancer patients in a recent study (Jansen et al., 2011) also reported positive experiences in their lives, as paradoxical as it may sound; with 64% of survivors reporting they experienced moderate to high levels of benefit finding.
Keywords: Cancer-research; Positive; Impact on patients